Coating film for COB (Chip On Board) surface treatment and preparation process thereof
By using a combination of titanium-containing polysiloxane and oyster shell powder-polymethylhydrosiloxane grafts in COB packaging glue, the problem of aging and warping of COB packaging glue at high temperatures is solved, and the packaging is improved The glue has high temperature and mechanical properties, and accelerates the curing process, optimizes packaging speed and production efficiency.
Patent Information
- Application Number
- CN202411803141.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing COB packaging materials are prone to aging, warping and cracking at high temperatures, and have a slow curing speed, which affects the packaging quality and production efficiency. The nanofillers and packaging glue have poor compatibility, making it difficult to effectively improve performance.
The COB encapsulation with titanium-containing polysiloxane and oyster shell powder-polymethylhydrogen siloxane graft combined with silicone elastomer microspheres is enhanced by the introduction of titanium atoms, and the thermal stability and mechanical properties are enhanced by modification. The treatment improves the hydrophobic properties and interface compatibility of oyster shell powder, and forms a network structure to speed up the curing process.
It significantly improves the high temperature resistance, mechanical properties and curing speed of COB packaging glue, reduces warpage and thermal expansion coefficient, and optimizes packaging speed and production efficiency.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic packaging adhesive, and more specifically, to a coating film for COB surface treatment and a preparation process thereof. Background Art
[0002] COB surface treatment usually refers to a protective or enhanced treatment of the chip and circuit board surface during the COB (Chip on Board) packaging process. This surface treatment operation mainly uses packaging glue materials with conductive, thermal, insulating or protective properties to coat the chip and circuit board surface.
[0003] At present, the commonly used encapsulation materials in COB encapsulation process are mainly epoxy resin encapsulation, polyurethane encapsulation and silicone encapsulation. These three encapsulation materials have their own advantages, but they also have certain limitations, such as large linear expansion coefficient and poor high temperature resistance. These problems are likely to cause the film to age faster after the encapsulation is cured, or warp and crack at high temperature, thereby affecting the bonding and coating ability of the film and the PCB board; in addition, the film is easily damaged under the action of external force, which may damage the chip or circuit board; in the encapsulation process, the encapsulation cures slowly, restricting the encapsulation speed and reducing production efficiency. In order to further improve the high temperature resistance, anti-aging performance and mechanical properties of the encapsulation, the more mature technology is to add nanofillers such as nano-silicon dioxide, nano-titanium dioxide, nano-zirconium oxide, etc. to the encapsulation. However, the compatibility of many nanofillers with encapsulation is usually not ideal, and it is easy to agglomerate, making it difficult to effectively exert the performance advantages of nanofillers, and thus the performance improvement effect of the encapsulation is limited. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides a coating for COB surface treatment and a preparation process thereof.
[0005] A coating for COB surface treatment, the coating is obtained by dispensing or pouring COB packaging glue on the packaged part and curing it; The raw materials of COB packaging glue include: component A and component B, and the mass ratio of component A to component B is 1: (1 to 1.5); The raw materials of component A include: 60 to 80 parts by weight of methyl vinyl silicone oil, 5 to 12 parts by weight of titanium-containing polysiloxane, 0.1 to 0.5 parts by weight of platinum water and 3 to 5 parts by weight of adhesive; The raw materials of component B include: 50 to 70 parts by weight of methyl vinyl MQ silicone resin, 8 to 15 parts by weight of organic silicone elastomer compound, 1 to 4 parts by weight of crosslinking agent and 0.1 to 0.6 parts by weight of inhibitor; The raw materials for preparing titanium-containing polysiloxane include: titanium tetrachloride alcohol solution and a mixed liquid obtained by mixing a colorless transparent liquid, dimethyl polysiloxane and hexamethyl phosphoric triamide in a volume ratio of (1-5): (1-5): (0.2-1), wherein the amount of titanium tetrachloride alcohol solution added is 0.4-1.2 times the volume of the mixed liquid; The raw materials for preparing the colorless transparent liquid include: α, ω-dihydroxy polydimethylsiloxane and a potassium hydroxide solution with a concentration of 0.1 mol / L, wherein the volume ratio of the α, ω-dihydroxy polydimethylsiloxane to the potassium hydroxide solution with a concentration of 0.1 mol / L is (1-3): (0.5-3); The raw materials for preparing the silicone elastomer composite include: oyster shell powder-polymethyl hydrogen siloxane grafted material, silane coupling agent, platinum water and silicone elastomer microspheres, wherein the mixing mass ratio of oyster shell powder-polymethyl hydrogen siloxane grafted material, silane coupling agent, platinum water and silicone elastomer microspheres is (10-60): (1-3): (0.2-1): (10-30): The raw materials for preparing the oyster shell powder-polymethylhydrogensiloxane grafted product include: modified oyster shell powder dispersion, polymethylhydrogensiloxane, dibutyltin dilaurate and silane coupling agent, wherein the mass ratio of the modified oyster shell powder dispersion, polymethylhydrogensiloxane, dibutyltin dilaurate and silane coupling agent is (10-15): (70-100): (0.8-1.5): (1-3), the modified oyster shell powder dispersion is obtained by mixing the modified oyster shell powder and xylene in a mass ratio of (1-3): (70-100), and the modified oyster shell powder is obtained by modifying the oyster shell powder with a silane coupling agent.
[0006] A preparation process of a coating for COB surface treatment comprises the following steps: Step S1: Preparation of titanium-containing polysiloxane, stirring α, ω-dihydroxy polydimethylsiloxane and potassium hydroxide solution for reaction, then vacuumizing, collecting the liquid generated by the reaction to obtain a colorless transparent liquid, heating the colorless transparent liquid, dimethyl polysiloxane and hexamethylphosphoric triamide for reaction, then dropping titanium tetrachloride alcohol solution into the mixture, stirring, reacting and rotary distilling to obtain titanium-containing polysiloxane; Step S2: Preparation of oyster shell powder-polymethylhydrogensiloxane grafted product, crushing oyster shell into oyster shell powder and modifying it with silane coupling agent, dispersing the modified oyster shell powder in xylene and heating and stirring with polymethylhydrogensiloxane, dibutyltin dilaurate and silane coupling agent to react, and after cooling, obtaining oyster shell powder-polymethylhydrogensiloxane grafted product; Step S3: Preparation of an organosilicon elastomer composite material, preparing organosilicon elastomer microspheres, heating and stirring oyster shell powder-polymethylhydrogensiloxane grafted material, silane coupling agent, platinum water and organosilicon elastomer microspheres, uniformly mixing and cooling, and then vacuum degassing and curing to obtain an organosilicon elastomer composite material; Step S4: Preparation of COB encapsulation glue and coating molding for COB surface treatment, methyl vinyl silicone oil, titanium-containing polysiloxane, platinum water and adhesive are mixed to obtain component A, methyl vinyl MQ silicone resin, silicone elastomer composite, cross-linking agent and inhibitor are stirred and mixed to obtain component B, component A and component B are mixed, and vacuum degassing is performed to obtain COB encapsulation glue, and the COB encapsulation glue is dispensed or poured on the part to be encapsulated, and after curing and molding, a coating is obtained.
[0007] Furthermore, step S1: preparation of titanium-containing polysiloxane specifically comprises the following steps: S1.1: α, ω-dihydroxy polydimethylsiloxane and a potassium hydroxide solution with a concentration of 0.1 mol / L are added to a reactor in a volume ratio of (1-3): (0.5-3), and heated and stirred under a nitrogen atmosphere. When the temperature reaches 100-130°C, the nitrogen gas is stopped from being introduced into the reactor, and the reactor is evacuated. When the vacuum degree reaches -0.09 to -0.07 MPa, the liquid generated by the reaction is collected. When the liquid aggregation speed decreases, the vacuum degree is adjusted to -0.1 to -0.15 MPa until no liquid is generated or aggregated, and a colorless transparent liquid is obtained; S1.2: Mix a colorless transparent liquid, dimethyl polysiloxane and hexamethylphosphoric acid triamide in a volume ratio of (1-5): (1-5): (0.2-1) to obtain a mixed liquid. Stir the mixed liquid for reaction for 1-3 hours under a nitrogen atmosphere at 100-120°C. Subsequently, lower the temperature to 60-80°C and dropwise add a titanium tetrachloride alcohol solution into the mixed liquid. The addition rate of the titanium tetrachloride alcohol solution is 0.5-1 mL / s, and the amount of the titanium tetrachloride alcohol solution added is 0.4-1.2 times the volume of the mixed liquid. After the addition of the titanium tetrachloride alcohol solution is completed, continue to stir the reaction for 4-6 hours. After rotary distillation, titanium-containing polysiloxane is obtained.
[0008] Furthermore, the titanium tetrachloride alcohol solution is prepared by mixing titanium tetrachloride, anhydrous isopropanol, anhydrous n-propanol and anhydrous ethanol in a volume ratio of (1-5): (30-45): (25-35): (25-35).
[0009] Further, step S2: preparation of oyster shell powder-polymethylhydrogensiloxane grafted material specifically comprises the following steps: S2.1: Wash, dry and crush the discarded oyster shells into coarse oyster shell powder, put the coarse oyster shell powder, steel balls and water in a mass ratio of 1: (0.5-2): (0.1-1) into a ball mill for wet grinding, the ball mill speed is 20-80 rpm, and the ball milling time is 18-24 h. After the ball milling, dry the obtained oyster shell powder at 90-110 ° C for 8-12 h, pass through a 120-150 mesh sieve, and obtain oyster shell powder; S2.2: mixing the oyster shell powder with anhydrous ethanol, and ultrasonically dispersing the mixture for 10 to 20 minutes, then adding a silane coupling agent, heating the mixture to 70 to 85° C., and stirring the mixture until the anhydrous ethanol is completely evaporated, thereby obtaining a modified oyster shell powder; S2.3: The modified oyster shell powder and xylene are mixed in a solid-liquid mass ratio of (1-3): (70-100), and ultrasonically dispersed for 10-20 minutes to obtain a modified oyster shell powder dispersion. Subsequently, the modified oyster shell powder dispersion, polymethylhydrogensiloxane, dibutyltin dilaurate and a silane coupling agent are added to a reaction vessel, stirred at 40-50°C for 2-3 hours, and cooled to room temperature to obtain an oyster shell powder-polymethylhydrogensiloxane graft.
[0010] Furthermore, the mixing mass ratio of oyster shell powder, anhydrous ethanol and silane coupling agent is (1-3): (50-100): (0.5-2).
[0011] Further, step S3: preparation of the silicone elastomer composite material specifically comprises the following steps: S3.1: In a water bath at 40 to 50° C., 1,1,3,3-tetramethyldisiloxane, isophorone diisocyanate and a mixed solvent are stirred and mixed in a mass ratio of (4 to 8): (4 to 10): (50 to 90), wherein the mixed solvent is prepared by mixing acetonitrile and acetone in a volume ratio of 2:1 to obtain a mixed solution; S3.2: dripping the mixed solution into a mixture prepared by mixing methyl vinyl silicone resin and pentaerythritol triacrylate in a volume ratio of 1:1, the amount of the mixed solution added is 0.5 to 1.5 times the volume of the mixture, after the dripping is completed, adding an acetonitrile aqueous solution with an acetonitrile mass fraction of 70%, the amount of the acetonitrile aqueous solution added is 1 to 1.5 times the total volume of the mixed solution and the mixture after mixing, leaving it to stand for 2 to 4 hours, filtering, and drying the filter residue to obtain silicone elastomer microspheres; S3.3: Place oyster shell powder-polymethylhydrogensiloxane graft, silane coupling agent and platinum water into a reactor, stir at room temperature for 40 to 60 minutes under a nitrogen atmosphere, add silicone elastomer microspheres into the reactor, raise the temperature to 50 to 80°C and continue stirring for 2 to 3 hours, mix evenly and cool, vacuum degas, pour into a demolding mold, and cure at 120 to 150°C for 1 to 3 hours to obtain a silicone elastomer composite.
[0012] Further, step S4: preparation of COB encapsulation glue and film forming for COB surface treatment specifically includes the following steps: S4.1: 60 to 80 parts by weight of methyl vinyl silicone oil, 5 to 12 parts by weight of titanium-containing polysiloxane, 0.1 to 0.5 parts by weight of platinum water, and 3 to 5 parts by weight of an adhesive are sequentially added into a blender, and stirred and mixed evenly under a nitrogen atmosphere to obtain component A; S4.2: 50 to 70 parts by weight of methyl vinyl MQ silicone resin, 8 to 15 parts by weight of silicone elastomer composite, 1 to 4 parts by weight of crosslinking agent, and 0.1 to 0.6 parts by weight of inhibitor are sequentially added into a blender, and stirred and mixed evenly under a nitrogen atmosphere to obtain component B; S4.3: Mix component A and component B in a mass ratio of 1: (1-1.5), perform vacuum degassing, and obtain a COB encapsulation adhesive; S4.4: Dispense or pour the COB encapsulation glue on the packaged part and perform curing. The temperature used for the curing is 80-120°C. After curing and forming, a coating is obtained.
[0013] Furthermore, the silane coupling agent is at least one of silane coupling agent A151, silane coupling agent KH-550, silane coupling agent KH-560 or silane coupling agent KH-570.
[0014] Furthermore, the adhesive is at least one of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, vinyltrimethoxysilane or γ-glycidyloxypropyltrimethoxysilane; the crosslinking agent is polymethylhydrogensiloxane; and the inhibitor is at least one of 1-ethynyl-1-cyclohexanol, 2-methyl-3-butynol-2-ol, 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol or 3,5-dimethyl-1-hexyn-3-ol.
[0015] The present invention has the following advantages: 1. In the present invention, titanium atoms are introduced into the structure of polysiloxane by polymerization reaction between α, ω-dihydroxy polydimethylsiloxane and titanium tetrachloride, so that the titanium atoms are evenly distributed in the polysiloxane chain and form chemical bonds with silicon atoms and oxygen atoms. The obtained titanium-containing polysiloxane can not only enhance the thermal stability of the siloxane chain by the introduction of titanium atoms, but also has good compatibility with methyl vinyl MQ silicone resin, which is beneficial to improve the high temperature resistance and mechanical properties of COB packaging glue by using titanium-containing polysiloxane, thereby improving the mechanical properties of the coating, and strengthening the high temperature resistance and anti-aging properties.
[0016] 2. In the present invention, the oyster shell powder is modified and the modified oyster shell powder is grafted with polymethylhydrogensiloxane. The polymethylhydrogensiloxane can improve the hydrophobicity of the oyster shell powder, reduce the hygroscopicity of the oyster shell powder, enhance the interfacial bonding force between the oyster shell powder and the polymer matrix, and improve its compatibility and dispersibility with the polymer matrix. The oyster shell powder component is then used to adjust the thermal expansion coefficient and mechanical properties of the COB encapsulation glue, so that the COB encapsulation glue has a low coating warpage and higher strength after curing.
[0017] 3. In the present invention, silicone elastomer microspheres and oyster shell powder-polymethylhydrogensiloxane grafts are cross-linked to form a network structure, and the obtained silicone elastomer composite has the characteristics of semi-liquid and semi-fluid. Adding the silicone elastomer composite to the COB encapsulation glue can effectively accelerate the curing process, shorten the curing time, and effectively increase the curing molding speed of the coating, thereby optimizing the encapsulation speed and improving production efficiency. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Example 1 A preparation process of a coating for COB surface treatment, specifically comprising the following steps: S1: Preparation of titanium-containing polysiloxane, S1.1: α, ω-dihydroxy polydimethylsiloxane and a potassium hydroxide solution with a concentration of 0.1 mol / L are added to a reactor in a volume ratio of 3:2, and heated and stirred under a nitrogen atmosphere. When the temperature reaches 120°C, the nitrogen gas is stopped from entering the reactor, and the reactor is evacuated. When the vacuum degree reaches -0.07 MPa, the liquid generated by the reaction is collected. When the liquid aggregation speed decreases, the vacuum degree is adjusted to -0.15 MPa until no liquid is generated and aggregated, and a colorless transparent liquid is obtained; S1.2: A colorless transparent liquid, dimethyl polysiloxane and hexamethyl phosphoric acid triamide are stirred and mixed in a volume ratio of 5:5:1 to obtain a mixed liquid. The mixed liquid is stirred and reacted for 2 hours under a nitrogen atmosphere at 120°C. Subsequently, the temperature is lowered to 80°C, and a titanium tetrachloride alcohol solution is dripped into the mixed liquid dropwise. The dropping speed of the titanium tetrachloride alcohol solution is 1 mL / s, wherein the titanium tetrachloride alcohol solution is prepared by mixing titanium tetrachloride, anhydrous isopropanol, anhydrous n-propanol and anhydrous ethanol in a volume ratio of 5:30:30:30. The amount of the titanium tetrachloride alcohol solution added is 0.8 times the volume of the mixed liquid. After the titanium tetrachloride alcohol solution is added dropwise, the stirring reaction is continued for 6 hours. After rotary distillation, titanium-containing polysiloxane is obtained. S2: Preparation of oyster shell powder-polymethylhydrogensiloxane grafted products, S2.1: Wash, dry and crush the discarded oyster shells into coarse oyster shell powder, put the coarse oyster shell powder, steel balls and water in a mass ratio of 1:1:1 into a ball mill for wet grinding, the ball milling speed is 60 rpm, and the ball milling time is 24 h. After the ball milling, the obtained oyster shell powder is dried at 110°C for 12 h, and passed through a 150-mesh sieve to obtain oyster shell powder; S2.2: Mix the oyster shell powder with anhydrous ethanol, and ultrasonically disperse for 20 minutes. Then, add the silane coupling agent KH-570, raise the temperature to 75°C, and stir the reaction until the anhydrous ethanol is completely volatilized to obtain a modified oyster shell powder, wherein the mixing mass ratio of the oyster shell powder, anhydrous ethanol and the silane coupling agent KH-570 is 3:90:2; S2.3: The modified oyster shell powder and xylene are mixed in a solid-liquid mass ratio of 3:100, and ultrasonically dispersed for 20 minutes to obtain a modified oyster shell powder dispersion. Subsequently, the modified oyster shell powder dispersion, polymethylhydrogensiloxane, dibutyltin dilaurate and silane coupling agent KH-570 are added to a reaction vessel, wherein the mass ratio of the modified oyster shell powder dispersion, polymethylhydrogensiloxane, dibutyltin dilaurate and silane coupling agent KH-570 is 15:100:1.5:3. The mixture is stirred at 45°C for 3 hours, and after cooling to room temperature, an oyster shell powder-polymethylhydrogensiloxane graft is obtained; S3: Preparation of silicone elastomer composites, S3.1: In a water bath at 50° C., 1,1,3,3-tetramethyldisiloxane, isophorone diisocyanate and a mixed solvent were stirred and mixed in a mass ratio of 8:8:70, wherein the mixed solvent was prepared by mixing acetonitrile and acetone in a volume ratio of 2:1 to obtain a mixed solution; S3.2: dripping the mixed solution into a mixture prepared by mixing methyl vinyl silicone resin and pentaerythritol triacrylate in a volume ratio of 1:1, the amount of the mixed solution added is 1.5 times the volume of the mixture, after the dripping is completed, adding an acetonitrile aqueous solution with an acetonitrile mass fraction of 70%, the amount of the acetonitrile aqueous solution added is 1 times the total volume of the mixed solution and the mixture, leaving it to stand for 3 hours, filtering, and drying the residue to obtain silicone elastomer microspheres; S3.3: Place oyster shell powder-polymethyl hydrogen siloxane graft, silane coupling agent KH-570 and platinum water into a reactor, stir at room temperature for 60 minutes under a nitrogen atmosphere, add silicone elastomer microspheres into the reactor, heat up to 80°C and continue stirring for 3 hours, the mixing mass ratio of oyster shell powder-polymethyl hydrogen siloxane graft, silane coupling agent KH-570, platinum water and silicone elastomer microspheres is 60:3:1:30, mix evenly and cool, vacuum degas, pour into a demolding mold, and cure at 150°C for 3 hours to obtain a silicone elastomer composite; S4: Preparation of COB encapsulation glue and lamination molding for COB surface treatment, S4.1: 80 parts by weight of methyl vinyl silicone oil, 12 parts by weight of titanium-containing polysiloxane, 0.5 parts by weight of platinum water, and 5 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane are added to a blender in sequence, and stirred and mixed evenly under a nitrogen atmosphere to obtain component A; S4.2: 60 parts by weight of methyl vinyl MQ silicone resin, 15 parts by weight of silicone elastomer composite, 4 parts by weight of polymethyl hydrogen siloxane, and 0.6 parts by weight of 1-ethynyl-1-cyclohexanol are sequentially added into a blender, and stirred and mixed evenly under a nitrogen atmosphere to obtain component B; S4.3: Mix component A and component B in a mass ratio of 1:1.2, and vacuum degas to obtain COB packaging glue; S4.4: Dispense or pour the COB encapsulation glue on the encapsulated part and perform curing. The temperature used for the curing is 120°C. After curing and forming, a coating is obtained.
[0020] Example 2 A preparation process of a coating for COB surface treatment, specifically comprising the following steps: S1: Preparation of titanium-containing polysiloxane, S1.1: α, ω-dihydroxy polydimethylsiloxane and a potassium hydroxide solution with a concentration of 0.1 mol / L are added to a reactor in a volume ratio of 3:2, and heated and stirred under a nitrogen atmosphere. When the temperature reaches 130°C, the nitrogen gas is stopped from entering the reactor, and the reactor is evacuated. When the vacuum degree reaches -0.07 MPa, the liquid generated by the reaction is collected. When the liquid aggregation speed decreases, the vacuum degree is adjusted to -0.1 MPa until no liquid is generated and aggregated, and a colorless transparent liquid is obtained; S1.2: A colorless transparent liquid, dimethyl polysiloxane and hexamethyl phosphoric acid triamide are stirred and mixed in a volume ratio of 5:5:1 to obtain a mixed liquid. The mixed liquid is stirred and reacted for 3 hours under a nitrogen atmosphere at 100°C. Subsequently, the temperature is lowered to 60°C, and a titanium tetrachloride alcohol solution is dripped into the mixed liquid dropwise. The dropping rate of the titanium tetrachloride alcohol solution is 0.5 mL / s, wherein the titanium tetrachloride alcohol solution is prepared by mixing titanium tetrachloride, anhydrous isopropanol, anhydrous n-propanol and anhydrous ethanol in a volume ratio of 5:30:30:30. The amount of the titanium tetrachloride alcohol solution added is 0.8 times the volume of the mixed liquid. After the titanium tetrachloride alcohol solution is added dropwise, the stirring reaction is continued for 4 hours. After rotary distillation, titanium-containing polysiloxane is obtained. S2: Preparation of oyster shell powder-polymethylhydrogensiloxane grafted products, S2.1: Wash, dry and crush the discarded oyster shells into coarse oyster shell powder, put the coarse oyster shell powder, steel balls and water in a mass ratio of 1:1:1 into a ball mill for wet grinding, the ball milling speed is 80 rpm, and the ball milling time is 18 h. After the ball milling, the obtained oyster shell powder is dried at 90 ° C for 8 h, and passed through a 150 mesh sieve to obtain oyster shell powder; S2.2: Mix the oyster shell powder with anhydrous ethanol, and ultrasonically disperse for 20 minutes. Then, add the silane coupling agent KH-570, raise the temperature to 85°C, and stir the reaction until the anhydrous ethanol is completely volatilized to obtain a modified oyster shell powder, wherein the mixing mass ratio of the oyster shell powder, anhydrous ethanol and the silane coupling agent KH-570 is 3:90:2; S2.3: The modified oyster shell powder and xylene are mixed in a solid-liquid mass ratio of 3:100, and ultrasonically dispersed for 20 minutes to obtain a modified oyster shell powder dispersion. Subsequently, the modified oyster shell powder dispersion, polymethylhydrogensiloxane, dibutyltin dilaurate and silane coupling agent KH-570 are added to a reaction vessel, wherein the mass ratio of the modified oyster shell powder dispersion, polymethylhydrogensiloxane, dibutyltin dilaurate and silane coupling agent KH-570 is 15:100:1.5:3. Stir at 50°C for 2 hours, and after cooling to room temperature, an oyster shell powder-polymethylhydrogensiloxane graft is obtained; S3: Preparation of silicone elastomer composites, S3.1: In a water bath at 40° C., 1,1,3,3-tetramethyldisiloxane, isophorone diisocyanate and a mixed solvent are stirred and mixed in a mass ratio of 8:8:70, wherein the mixed solvent is prepared by mixing acetonitrile and acetone in a volume ratio of 2:1 to obtain a mixed solution; S3.2: dripping the mixed solution into a mixture prepared by mixing methyl vinyl silicone resin and pentaerythritol triacrylate in a volume ratio of 1:1, the amount of the mixed solution added is 1.5 times the volume of the mixture, after the dripping is completed, adding an acetonitrile aqueous solution with an acetonitrile mass fraction of 70%, the amount of the acetonitrile aqueous solution added is 1 times the total volume of the mixed solution and the mixture, leaving it to stand for 2 hours, filtering, and drying the residue to obtain silicone elastomer microspheres; S3.3: Place oyster shell powder-polymethyl hydrogen siloxane graft, silane coupling agent KH-570 and platinum water into a reactor, stir at room temperature for 40 minutes under a nitrogen atmosphere, add silicone elastomer microspheres into the reactor, heat up to 60°C and continue stirring for 3 hours, the mixing mass ratio of oyster shell powder-polymethyl hydrogen siloxane graft, silane coupling agent KH-570, platinum water and silicone elastomer microspheres is 60:3:1:30, mix evenly and cool, vacuum degas, pour into a demolding mold, and cure at 120°C for 1 hour to obtain a silicone elastomer composite; S4: Preparation of COB encapsulation glue and lamination molding for COB surface treatment, S4.1: 80 parts by weight of methyl vinyl silicone oil, 12 parts by weight of titanium-containing polysiloxane, 0.5 parts by weight of platinum water, and 5 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane are added to a blender in sequence, and stirred and mixed evenly under a nitrogen atmosphere to obtain component A; S4.2: 60 parts by weight of methyl vinyl MQ silicone resin, 15 parts by weight of silicone elastomer composite, 4 parts by weight of polymethyl hydrogen siloxane, and 0.6 parts by weight of 1-ethynyl-1-cyclohexanol are sequentially added into a blender, and stirred and mixed evenly under a nitrogen atmosphere to obtain component B; S4.3: Mix component A and component B in a mass ratio of 1:1.2, and vacuum degas to obtain COB packaging glue; S4.4: Dispense or pour the COB encapsulation glue on the packaged part and perform curing. The temperature used for the curing is 100°C. After curing and forming, a coating is obtained.
[0021] Example 3 A preparation process of a coating for COB surface treatment, specifically comprising the following steps: S1: Preparation of titanium-containing polysiloxane, S1.1: α, ω-dihydroxy polydimethylsiloxane and a potassium hydroxide solution with a concentration of 0.1 mol / L are added to a reactor in a volume ratio of 1:1, and heated and stirred under a nitrogen atmosphere. When the temperature reaches 120°C, the nitrogen gas is stopped from being introduced into the reactor, and the reactor is evacuated. When the vacuum degree reaches -0.07 MPa, the liquid generated by the reaction is collected. When the liquid aggregation speed decreases, the vacuum degree is adjusted to -0.15 MPa until no liquid is generated and aggregated, and a colorless transparent liquid is obtained; S1.2: A colorless transparent liquid, dimethyl polysiloxane and hexamethyl phosphoric acid triamide are stirred and mixed in a volume ratio of 1:1:0.5 to obtain a mixed liquid. The mixed liquid is stirred and reacted for 2 hours under a nitrogen atmosphere at 120°C. Subsequently, the temperature is lowered to 80°C, and a titanium tetrachloride alcohol solution is dripped into the mixed liquid dropwise. The dropping speed of the titanium tetrachloride alcohol solution is 1 mL / s, wherein the titanium tetrachloride alcohol solution is prepared by mixing titanium tetrachloride, anhydrous isopropanol, anhydrous n-propanol and anhydrous ethanol in a volume ratio of 1:30:25:25. The amount of the titanium tetrachloride alcohol solution added is 1.2 times the volume of the mixed liquid. After the titanium tetrachloride alcohol solution is added dropwise, the stirring reaction is continued for 6 hours. After rotary distillation, titanium-containing polysiloxane is obtained. S2: Preparation of oyster shell powder-polymethylhydrogensiloxane grafted products, S2.1: Wash, dry and crush the discarded oyster shells into coarse oyster shell powder, put the coarse oyster shell powder, steel balls and water in a mass ratio of 1:1:1 into a ball mill for wet grinding, the ball milling speed is 60 rpm, and the ball milling time is 24 h. After the ball milling, the obtained oyster shell powder is dried at 110°C for 12 h, and passed through a 150-mesh sieve to obtain oyster shell powder; S2.2: Mix the oyster shell powder with anhydrous ethanol, and ultrasonically disperse for 20 minutes. Then, add the silane coupling agent KH-570, raise the temperature to 75°C, and stir the reaction until the anhydrous ethanol is completely volatilized to obtain a modified oyster shell powder, wherein the mixing mass ratio of the oyster shell powder, anhydrous ethanol and the silane coupling agent KH-570 is 1:70:2; S2.3: The modified oyster shell powder and xylene are mixed in a solid-liquid mass ratio of 1:70, and ultrasonically dispersed for 20 minutes to obtain a modified oyster shell powder dispersion. Subsequently, the modified oyster shell powder dispersion, polymethylhydrogensiloxane, dibutyltin dilaurate and silane coupling agent KH-570 are added to a reaction vessel, wherein the mass ratio of the modified oyster shell powder dispersion, polymethylhydrogensiloxane, dibutyltin dilaurate and silane coupling agent KH-570 is 10:70:0.8:1, and stirred at 45°C for 3 hours. After cooling to room temperature, oyster shell powder-polymethylhydrogensiloxane grafted product is obtained; S3: Preparation of silicone elastomer composites, S3.1: In a water bath at 50° C., 1,1,3,3-tetramethyldisiloxane, isophorone diisocyanate and a mixed solvent are stirred and mixed in a mass ratio of 5:6:50, wherein the mixed solvent is prepared by mixing acetonitrile and acetone in a volume ratio of 2:1 to obtain a mixed solution; S3.2: dripping the mixed solution into a mixture prepared by mixing methyl vinyl silicone resin and pentaerythritol triacrylate in a volume ratio of 1:1, the amount of the mixed solution added is 1 times the volume of the mixture, after the dripping is completed, adding an acetonitrile aqueous solution with an acetonitrile mass fraction of 70%, the amount of the acetonitrile aqueous solution added is 1.5 times the total volume of the mixed solution and the mixture, leaving it to stand for 3 hours, filtering, and drying the residue to obtain silicone elastomer microspheres; S3.3: Place oyster shell powder-polymethylhydrogensiloxane grafted product, silane coupling agent KH-570 and platinum water into a reactor, stir at room temperature for 60 minutes under a nitrogen atmosphere, add silicone elastomer microspheres into the reactor, heat up to 80°C and continue stirring for 3 hours, the mixing mass ratio of oyster shell powder-polymethylhydrogensiloxane grafted product, silane coupling agent KH-570, platinum water and silicone elastomer microspheres is 10:1:0.2:10, mix evenly and cool, vacuum degas, pour into a demolding mold, and cure at 150°C for 3 hours to obtain a silicone elastomer composite; S4: Preparation of COB encapsulation glue and lamination molding for COB surface treatment, S4.1: 80 parts by weight of methyl vinyl silicone oil, 12 parts by weight of titanium-containing polysiloxane, 0.5 parts by weight of platinum water, and 5 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane are added to a blender in sequence, and stirred and mixed evenly under a nitrogen atmosphere to obtain component A; S4.2: 60 parts by weight of methyl vinyl MQ silicone resin, 15 parts by weight of silicone elastomer composite, 4 parts by weight of polymethyl hydrogen siloxane, and 0.6 parts by weight of 1-ethynyl-1-cyclohexanol are sequentially added into a blender, and stirred and mixed evenly under a nitrogen atmosphere to obtain component B; S4.3: Mix component A and component B in a mass ratio of 1:1.2, and vacuum degas to obtain COB packaging glue; S4.4: Dispense or pour the COB encapsulation glue on the encapsulated part and perform curing. The temperature used for the curing is 120°C. After curing and forming, a coating is obtained.
[0022] Comparative Example 1 Compared with Example 1, the difference of Comparative Example 1 is that the titanium-containing polysiloxane in the COB packaging adhesive component is removed, and the other components and steps remain unchanged to prepare the COB packaging adhesive, which is recorded as Comparative Example 1.
[0023] Comparative Example 2 Compared with Example 1, the difference of Comparative Example 2 is that the titanium-containing polysiloxane in the COB packaging glue component is replaced with an equal weight portion of nano titanium dioxide powder (particle size of 50 nm), and the other components and steps remain unchanged to prepare the COB packaging glue, which is recorded as Comparative Example 2.
[0024] Comparative Example 3 Compared with Example 1, the difference of Comparative Example 3 is that step S2 is removed, the oyster shell powder-polymethyl hydrogen siloxane graft in step S3.3 is replaced by polymethyl hydrogen siloxane, and the other steps remain unchanged to prepare COB packaging glue, which is recorded as Comparative Example 3.
[0025] Comparative Example 4 Compared with Example 1, the difference of Comparative Example 4 is that step S3 is removed, and the silicone elastomer composite in the COB encapsulation glue component is replaced with an equal weight portion of oyster shell powder-polymethylhydrogensiloxane grafted material, and the other components and steps remain unchanged to prepare the COB encapsulation glue, which is recorded as Comparative Example 4.
[0026] Comparative Example 5 Compared with Example 1, the difference of Comparative Example 5 is that step S3.3 is removed, the silicone elastomer composite in the COB encapsulation glue component is replaced with an equal weight portion of silicone elastomer microspheres, and the other components and steps remain unchanged to prepare the COB encapsulation glue, which is recorded as Comparative Example 5.
[0027] Performance Testing The COB packaging adhesives obtained in Examples 1-3 and Comparative Examples 1-5 were cured at 120° C. to obtain test samples. The following performance tests were performed on the obtained test samples and the test results were recorded.
[0028] Mechanical properties: 5 test samples were taken in Examples 1-3 and Comparative Examples 1-5, and the tensile strength test was performed on each test sample according to GB / T528-2009. The average value of the test results of each group of test samples was taken. The tensile strength test results are shown in Table 1; High temperature resistance: According to GB / T1036-2008, the thermal expansion coefficient of each group of test samples was tested using a dynamic mechanical tester. The test temperature was -40 to 150°C. The thermal expansion coefficient test results are shown in Table 1. Warpage: warpage test was conducted in accordance with IPC-TM-6502.4.22.4. Five test samples were taken from each group and cut into squares with a side length of 7.07 cm and a diagonal length of 10 cm. The cut test samples were reflowed onto the circuit board at 270°C to test the circuit board warpage. The warpage = warpage height / diagonal length × 100%. The average test results of each group of test samples were taken. The warpage test results are shown in Table 1. Curing efficiency: According to GB / T16584-1996, the curing efficiency of the COB encapsulation glue obtained in Examples 1-3 and Comparative Examples 1-5 was tested using a rotorless rubber processing analyzer. The time required for each group of COB encapsulation glue to reach 90% curing degree was tested. The test temperature was 120° C. The curing test results are shown in Table 1. Table 1:
[0029] As shown in Table 1, the tensile strength and warpage results of the test samples prepared by using the COB encapsulation adhesive of Examples 1-3 are significantly better than those of Comparative Examples 1-5, and the thermal expansion coefficient is also smaller and the curing time is also shorter. It is shown that compared with the direct addition of nano-titanium dioxide, the addition of titanium-containing polysiloxane to the COB encapsulation adhesive can more effectively improve the tensile strength of the COB encapsulation adhesive and reduce the thermal expansion coefficient of the COB encapsulation adhesive, thereby enhancing the high temperature resistance and mechanical properties of the COB encapsulation adhesive, reducing the warpage of the coating, and then strengthening the mechanical properties, high temperature resistance and anti-aging properties of the coating; and, by adding a silicone elastomer composite formed by cross-linking silicone elastomer microspheres and oyster shell powder-polymethylhydrogensiloxane grafts to the COB encapsulation adhesive, not only can the oyster shell powder component be used to further reduce the thermal expansion coefficient of the COB encapsulation adhesive and improve the tensile strength of the COB encapsulation adhesive, but also the curing molding speed can be effectively increased and the curing time can be shortened.
[0030] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all such improvements and changes should fall within the scope of protection of the appended claims of the present invention. Parts not described in detail in this specification belong to the prior art known to those skilled in the art.
Claims
1. A coating for COB surface treatment, characterized in that: The coating is obtained by dispensing or pouring COB packaging glue on the packaged part and curing it; The raw materials of COB packaging glue include: component A and component B, and the mass ratio of component A to component B is 1: (1 to 1.5); The raw materials of component A include: 60 to 80 parts by weight of methyl vinyl silicone oil, 5 to 12 parts by weight of titanium-containing polysiloxane, 0.1 to 0.5 parts by weight of platinum water and 3 to 5 parts by weight of adhesive; The raw materials of component B include: 50 to 70 parts by weight of methyl vinyl MQ silicone resin, 8 to 15 parts by weight of organic silicone elastomer compound, 1 to 4 parts by weight of crosslinking agent and 0.1 to 0.6 parts by weight of inhibitor; The raw materials for preparing titanium-containing polysiloxane include: titanium tetrachloride alcohol solution and a mixed liquid obtained by mixing a colorless transparent liquid, dimethyl polysiloxane and hexamethyl phosphoric triamide in a volume ratio of (1-5): (1-5): (0.2-1), wherein the amount of titanium tetrachloride alcohol solution added is 0.4-1.2 times the volume of the mixed liquid; The raw materials for preparing the colorless transparent liquid include: α, ω-dihydroxy polydimethylsiloxane and a potassium hydroxide solution with a concentration of 0.1 mol / L, wherein the volume ratio of the α, ω-dihydroxy polydimethylsiloxane to the potassium hydroxide solution with a concentration of 0.1 mol / L is (1-3): (0.5-3); The raw materials for preparing the silicone elastomer composite include: oyster shell powder-polymethyl hydrogen siloxane grafted material, silane coupling agent, platinum water and silicone elastomer microspheres, wherein the mixing mass ratio of oyster shell powder-polymethyl hydrogen siloxane grafted material, silane coupling agent, platinum water and silicone elastomer microspheres is (10-60): (1-3): (0.2-1): (10-30): The raw materials for preparing the oyster shell powder-polymethylhydrogensiloxane grafted product include: modified oyster shell powder dispersion, polymethylhydrogensiloxane, dibutyltin dilaurate and silane coupling agent, wherein the mass ratio of the modified oyster shell powder dispersion, polymethylhydrogensiloxane, dibutyltin dilaurate and silane coupling agent is (10-15): (70-100): (0.8-1.5): (1-3), the modified oyster shell powder dispersion is obtained by mixing the modified oyster shell powder and xylene in a mass ratio of (1-3): (70-100), and the modified oyster shell powder is obtained by modifying the oyster shell powder with a silane coupling agent.
2. A process for preparing a coating for COB surface treatment according to claim 1, characterized in that: The following steps are involved: Step S1: Preparation of titanium-containing polysiloxane, stirring α, ω-dihydroxy polydimethylsiloxane and potassium hydroxide solution for reaction, then vacuumizing, collecting the liquid generated by the reaction to obtain a colorless transparent liquid, heating the colorless transparent liquid, dimethyl polysiloxane and hexamethylphosphoric triamide for reaction, then dropping titanium tetrachloride alcohol solution into the mixture, stirring, reacting and rotary distilling to obtain titanium-containing polysiloxane; Step S2: Preparation of oyster shell powder-polymethylhydrogensiloxane grafted product, crushing oyster shell into oyster shell powder and modifying it with silane coupling agent, dispersing the modified oyster shell powder in xylene and heating and stirring with polymethylhydrogensiloxane, dibutyltin dilaurate and silane coupling agent to react, and after cooling, obtaining oyster shell powder-polymethylhydrogensiloxane grafted product; Step S3: Preparation of an organosilicon elastomer composite material, preparing organosilicon elastomer microspheres, heating and stirring oyster shell powder-polymethylhydrogensiloxane grafted material, silane coupling agent, platinum water and organosilicon elastomer microspheres, uniformly mixing and cooling, and then vacuum degassing and curing to obtain an organosilicon elastomer composite material; Step S4: Preparation of COB encapsulation glue and coating molding for COB surface treatment, methyl vinyl silicone oil, titanium-containing polysiloxane, platinum water and adhesive are mixed to obtain component A, methyl vinyl MQ silicone resin, silicone elastomer composite, cross-linking agent and inhibitor are stirred and mixed to obtain component B, component A and component B are mixed, and vacuum degassing is performed to obtain COB encapsulation glue, and the COB encapsulation glue is dispensed or poured on the part to be encapsulated, and after curing and molding, a coating is obtained.
3. The process for preparing a coating for COB surface treatment according to claim 2, characterized in that: Step S1: Preparation of titanium-containing polysiloxane, specifically comprising the following steps: S1.1: α, ω-dihydroxy polydimethylsiloxane and a potassium hydroxide solution with a concentration of 0.1 mol / L are added to a reactor in a volume ratio of (1-3): (0.5-3), and heated and stirred under a nitrogen atmosphere. When the temperature reaches 100-130°C, the nitrogen gas is stopped from being introduced into the reactor, and the reactor is evacuated. When the vacuum degree reaches -0.09 to -0.07 MPa, the liquid generated by the reaction is collected. When the liquid aggregation speed decreases, the vacuum degree is adjusted to -0.1 to -0.15 MPa until no liquid is generated or aggregated, and a colorless transparent liquid is obtained; S1.2: Mix a colorless transparent liquid, dimethyl polysiloxane and hexamethylphosphoric acid triamide in a volume ratio of (1-5): (1-5): (0.2-1) to obtain a mixed liquid. Stir the mixed liquid for reaction for 1-3 hours under a nitrogen atmosphere at 100-120°C. Subsequently, lower the temperature to 60-80°C and dropwise add a titanium tetrachloride alcohol solution into the mixed liquid. The addition rate of the titanium tetrachloride alcohol solution is 0.5-1 mL / s, and the amount of the titanium tetrachloride alcohol solution added is 0.4-1.2 times the volume of the mixed liquid. After the addition of the titanium tetrachloride alcohol solution is completed, continue to stir the reaction for 4-6 hours. After rotary distillation, titanium-containing polysiloxane is obtained.
4. The process for preparing a coating for COB surface treatment according to claim 3, characterized in that: The titanium tetrachloride alcohol solution is prepared by mixing titanium tetrachloride, anhydrous isopropanol, anhydrous n-propanol and anhydrous ethanol in a volume ratio of (1-5): (30-45): (25-35): (25-35).
5. The process for preparing a coating for COB surface treatment according to claim 4, characterized in that: Step S2: Preparation of oyster shell powder-polymethylhydrogensiloxane grafted material, specifically comprising the following steps: S2.1: Wash, dry and crush the discarded oyster shells into coarse oyster shell powder, put the coarse oyster shell powder, steel balls and water in a mass ratio of 1: (0.5-2): (0.1-1) into a ball mill for wet grinding, the ball mill speed is 20-80 rpm, and the ball milling time is 18-24 h. After the ball milling, dry the obtained oyster shell powder at 90-110 ° C for 8-12 h, pass through a 120-150 mesh sieve, and obtain oyster shell powder; S2.2: mixing the oyster shell powder with anhydrous ethanol, and ultrasonically dispersing the mixture for 10 to 20 minutes, then adding a silane coupling agent, heating the mixture to 70 to 85° C., and stirring the mixture until the anhydrous ethanol is completely evaporated, thereby obtaining a modified oyster shell powder; S2.3: The modified oyster shell powder and xylene are mixed in a solid-liquid mass ratio of (1-3): (70-100), and ultrasonically dispersed for 10-20 minutes to obtain a modified oyster shell powder dispersion. Subsequently, the modified oyster shell powder dispersion, polymethylhydrogensiloxane, dibutyltin dilaurate and a silane coupling agent are added to a reaction vessel, stirred at 40-50°C for 2-3 hours, and cooled to room temperature to obtain an oyster shell powder-polymethylhydrogensiloxane graft.
6. The process for preparing a coating for COB surface treatment according to claim 5, characterized in that: The mixing mass ratio of oyster shell powder, anhydrous ethanol and silane coupling agent is (1-3): (50-100): (0.5-2).
7. The process for preparing a coating for COB surface treatment according to claim 6, characterized in that: Step S3: Preparation of the silicone elastomer composite, specifically comprising the following steps: S3.1: In a water bath at 40 to 50° C., 1,1,3,3-tetramethyldisiloxane, isophorone diisocyanate and a mixed solvent are stirred and mixed in a mass ratio of (4 to 8): (4 to 10): (50 to 90), wherein the mixed solvent is prepared by mixing acetonitrile and acetone in a volume ratio of 2:1 to obtain a mixed solution; S3.2: dripping the mixed solution into a mixture prepared by mixing methyl vinyl silicone resin and pentaerythritol triacrylate in a volume ratio of 1:1, the amount of the mixed solution added is 0.5 to 1.5 times the volume of the mixture, after the dripping is completed, adding an acetonitrile aqueous solution with an acetonitrile mass fraction of 70%, the amount of the acetonitrile aqueous solution added is 1 to 1.5 times the total volume of the mixed solution and the mixture after mixing, leaving it to stand for 2 to 4 hours, filtering, and drying the filter residue to obtain silicone elastomer microspheres; S3.3: Place oyster shell powder-polymethylhydrogensiloxane graft, silane coupling agent and platinum water into a reactor, stir at room temperature for 40 to 60 minutes under a nitrogen atmosphere, add silicone elastomer microspheres into the reactor, raise the temperature to 50 to 80°C and continue stirring for 2 to 3 hours, mix evenly and cool, vacuum degas, pour into a demolding mold, and cure at 120 to 150°C for 1 to 3 hours to obtain a silicone elastomer composite.
8. The process for preparing a coating for COB surface treatment according to claim 7, characterized in that: Step S4: Preparation of COB encapsulation glue and film forming for COB surface treatment, specifically including the following steps: S4.1: 60 to 80 parts by weight of methyl vinyl silicone oil, 5 to 12 parts by weight of titanium-containing polysiloxane, 0.1 to 0.5 parts by weight of platinum water, and 3 to 5 parts by weight of an adhesive are sequentially added into a blender, and stirred and mixed evenly under a nitrogen atmosphere to obtain component A; S4.2: 50 to 70 parts by weight of methyl vinyl MQ silicone resin, 8 to 15 parts by weight of silicone elastomer composite, 1 to 4 parts by weight of crosslinking agent, and 0.1 to 0.6 parts by weight of inhibitor are sequentially added into a blender, and stirred and mixed evenly under a nitrogen atmosphere to obtain component B; S4.3: Mix component A and component B in a mass ratio of 1: (1-1.5), perform vacuum degassing, and obtain a COB encapsulation adhesive; S4.4: Dispense or pour the COB encapsulation glue on the encapsulated part and perform curing. The temperature used for the curing is 80-120°C. After curing and forming, a coating is obtained.
9. The process for preparing a coating for COB surface treatment according to claim 8, characterized in that: The silane coupling agent is at least one of silane coupling agent A151, silane coupling agent KH-550, silane coupling agent KH-560 or silane coupling agent KH-570.
10. The process for preparing a coating for COB surface treatment according to claim 9, characterized in that: The adhesive is at least one of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, vinyltrimethoxysilane or γ-glycidyloxypropyltrimethoxysilane; the crosslinking agent is polymethylhydrogensiloxane; and the inhibitor is at least one of 1-ethynyl-1-cyclohexanol, 2-methyl-3-butynol-2-ol, 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol or 3,5-dimethyl-1-hexyn-3-ol.
Citation Information
Patent Citations
Preparation method for silicon-titanium polymer capable of being used as additive
CN104774334A
High-temperature-resistant COB packaging adhesive and preparation method thereof
CN116589973A
High-strength flame-retardant room-temperature vulcanized silicone rubber
CN117586629A
Curable silicone composition, cured object obtained therefrom, and optical semiconductor device
WO2016038836A1
Cited By
Mini LED packaging adhesive film and application
CN120365863A
Mini LED encapsulation adhesive film and application
CN120365863B